Turbulent forced convection of nanofluid over a heated shallow cavity in a duct - Abdellahoum, Chahrazed; Mataoui, Amina; Öztop, Hakan Fehmi (Elsevier Science Bv, 2015)
This work presents a numerical investigation of turbulent forced convection of a nanofluid over a heated cavity in a horizontal duct. The objective of this study is to show the effects of nanofluid on-heat transfer in such a configuration. The two-dimensional Cartesian coordinate system is used to solve the governing equations which are conservations of mass, momentum and energy. The numerical predictions based on finite volume method are performed by ANSYS FLUENT 14.0 CFD code. Numerical simulations are carried out for pure water and four different nanofluids (water-Cu, water-CuO,water-Ag and water-Al2O3). The results are analyzed through the thermal and dynamical fields with a particular interest to the kinetic energy, skin friction coefficient and Nusselt number evolutions. The range of parameters of Reynolds number is 40,000 Re 100,000 and different nanopartide volume fractions. The maximum shear stress is obtained for the lightest nanoparticle of smaller thermal conductivity (Al2O3). It is found that the average Nusselt number increases with the volume fraction of nanopartides for the whole tested range of Reynolds number. The nanoparticle type on average Nusselt number has an insignificant effect; the smallest values are obtained for the heavier particle with greatest value of thermal conductivity (Ag). Two correlations of average Nusselt number versus Reynolds number and volume fraction of each type of nanopartides over the cavity wall are proposed in this paper. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Nanofluids; Separated flows; Heat transfer; CED; Turbulence; Cavity; Skin friction coefficient; Nusselt number; Particle mass; Particle conductivity